Schorzenia w obrębie stawu łokciowego. Łokieć teniststy - schorzenie i współczesne metody leczenia = Diseases within the elbow joint. Tennis elbow - condition and modern methods of treatment - Joanna Siminska; Katarzyna Pietkun; Karol Ogurkowski; Joanna Stocka; Jolanta Dejewska; Krystyna Nowacka; Wojciech Hagner (Kazimierz Wielki University, 2015)
Siminska Joanna, Pietkun Katarzyna, Ogurkowski Karol, Stocka Joanna, Dejewska Jolanta, Nowacka Krystyna, Hagner Wojciech. Schorzenia w obrębie stawu łokciowego. Łokieć tenisisty - schorzenie i współczesne metody leczenia = Diseases within the elbow joint. Tennis elbow - condition and modern methods of treatment. Journal of Education, Health and Sport. 2015;5(4):205-218. ISSN 2391-8306. DOI: 10.5281/zenodo.16769 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%284%29%3A205-218 https://pbn.nauka.gov.pl/works/554266 http://dx.doi.org/10.5281/zenodo.16769 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.02.2015. Revised 27.03.2015. Accepted: 10.04.2015.   SCHORZENIA W OBRĘBIE STAWU ŁOKCIOWEGO. ŁOKIEĆ TENISISTY - SCHORZENIE I WSPÓŁCZESNE METODY LECZENIA DISEASES WITHIN THE ELBOW JOINT. TENNIS ELBOW - CONDITION AND MODERN METHODS OF TREATMENT   Siminska Joanna, Pietkun Katarzyna, Ogurkowski Karol, Stocka Joanna, Dejewska Jolanta, Nowacka Krystyna, Hagner Wojciech   Katedra i Klinika Rehabilitacji Collegium Medicum UMK w Bydgoszczy   Streszczenie   Według najnowszych danych Światowej Organizacji Zdrowia zauważyć należy, iż że wśród wszystkich obrażeń układu mięśniowo-szkieletowego prawie połowa to urazy tkanek miękkich (wraz ze ścięgnami i więzadłami), które często prowadzą one do powstawania przewlekłych dolegliwości  bólowych, ograniczenia ruchomości a  nawet niepełnosprawności. Ciągły rozwój medycyny oraz postęp technologiczny umożliwiają lepsze poznanie schorzeń układu mięśniowo-szkieletowego, ale również znalezienie najlepszych sposobów kompleksowej rehabilitacji. Jednym z obecnie najczęstszych urazów jest zapalenie nadkłykcia bocznego kości ramiennej, popularnie zwane "łokciem tenisisty". Pacjent z tym schorzeniem zgłasza się z odczuwanym bólem, który  jest spowodowany zwyrodnieniem w okolicy ścięgna prostowników. Omówiono również  najczęstsze urazy, które  dotyczą stawu łokciowego. Obecnie możemy wyróżnić kilka  metod leczenia schorzenia zapalenia nadkłykcia bocznego kości ramiennej m. in. polegające na ostrzykiwaniu miejsca sprawiającego ból: pełną krwią, sterydami oraz płukanymi płytkami krwi. Ponadto możemy stosować także  terapię falami uderzeniowymi oraz zabieg koblacji topaz.   Słowa kluczowe: łokieć tenisisty, leczenie, dolegliwości bólowe nadkłykcia bocznego kości ramiennej. Abstract According to the latest World Health Organization data that should be noted that among all the injuries of the musculoskeletal system, nearly half of the soft tissue injuries (along with the tendons and ligaments), which often lead to the formation of chronic pain disorders, limitation of movable property and even disability. The continuous development of the medicine and technological advances make it possible to better know the conditions of the musculoskeletal system, but also to find the best ways for comprehensive rehabilitation. One of the currently most common injuries is inflammation of the lateral epicondyle of the humerus, commonly referred to as "tennis elbow". A patient with this condition shall be reported with felt pain, which is caused by degeneration of the extensor tendons in the area. Also discusses the most common injuries that affect the elbow joint. Now we can distinguish a number of treatments for diseases of inflammation of the lateral epicondyle of the humerus, among others, consisting of injections space causing pain: full blood, steroids and washed platelets. In addition, we can also be used with shock wave therapy and treatment coblation topaz. Keywords: tennis elbow, treatment, humeral lateral epicondyle aches and pains.